Validation of the short version of the obsessive compulsive spectrum questionnaire - Dell’Osso, Liliana; Nardi, Benedetta; Bonelli, Chiara; Gravina, Davide; Benedetti, Francesca; Del Prete, Luca; Massimetti, Gabriele; Amatori, Giulia; Carpita, Barbara; Cremone, Ivan Mirko (Frontiers in Psychology, 2023)
Aim: in the recent years, a growing body of literature stressed the importance of a dimensional perspective on mental disorders. In particular, the conceptualization of an obsessive-compulsive spectrum appears to be in line with the very first descriptions of Obsessive-Compulsive Disorder and has been partially acknowledged by the inclusion of the “OCD-spectrum related syndromes and disorders” section in the DSM-5. The current study aims to determine the psychometric properties of the Obsessive-Compulsive Spectrum – Short Version (OBS-SV), a new questionnaire specifically tailored to assess the spectrum of Obsessive-compulsive symptoms, from full blown forms to subthreshold ones. Methods: 43 subjects with a clinical diagnosis of OCD according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-5); 42 subjects with a clinical diagnosis of social anxiety disorder (SAD), and 60 individuals without current or lifetime mental disorders (HC) were recruited from the Psychiatric Clinic of the University of Pisa. Subjects were assessed with the SCID-5, the Yale Brown Obsessive Compulsive Scale (Y-BOCS) and the OBS-SV. Results: OBS-SV demonstrated a high level of internal consistency and the test-retest reliability for total and domain scores was excellent. OBS-SV domain scores were positively and significantly correlated with each other (p < 0.001), with Pearson’s coefficients ranging from 0.771 to 0.943. All the OBS-SV domain scores were highly correlated with the OBS-SV total score. The correlation coefficients between OBS-SV and alternative measures of OCS appeared all significant and positive. Significant differences among diagnostic groups on both OBS-SV domains and total scores were found. OBS-SV total score increased significantly and progressively from HCs, to the SAD up to the OC group which showed the highest values. Conclusion: The OBS-SV showed excellent internal consistency and test-retest reliability and strong convergent validity with alternative dimensional measures of OCD. The questionnaire performed differently among the three diagnostic groups, with an increasing score gradient from HC to patients with SAD to those with OCD.